Network Investment and the Threat of Regulation – Preventing Monopoly Exploitation or Infrastructure Construction? - Ulrich Blum; Christian Growitsch; Niels Krap (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
In summer 2005, the German telecommunication incumbent Deutsche Telekom announced its plans to build a new broadband fibre optics network. Deutsche Telekom decided as precondition for this new network not to be regulated with respect to pricing and third party access. To develop a regulator's strategy that allows investments and prevents monopolistic prices at the same time, we model an incumbent's decision problem under a threat of regulation in a game-theoretical context. The decision whether to invest or not depends on the probability of regulation and its assumed impact on investment returns. Depending on the incumbent's expectation on these parameters, he will decide if the investment is favourable, and which price to best set. This price is below a non-regulated profit maximising price, since the incumbent tries to circumvent regulation. Thus, we show that the mere threat of a regulator's intervention might prevent supernormal profits without actual price regulation. The regulator, on the other hand, an influence both investment decision and the incumbent's price via his signals on regulation probability and price. These signals can be considered optimal, if they simultaneously allow investment and minimize the incumbent's price. – – Im Sommer 2005 gab die Deutsche Telekom ihre Planungen für den Aufbau eines neuen Glasfaserbreitbandkabelnetzes bekannt. Sie stellte dabei zur Bedingung, daß dieses Netz weder preislich noch hinsichtlich des Netzzugangs Dritter reguliert werden sollte. Um eine Regulierungsstrategie zu definieren, die gleichzeitig die Investition ermöglicht und monopolistische Preise verhindert, wird in diesem Beitrag ein Modell entwickelt, das das Entscheidungsproblem des Marktsassen unter Regulierungsandrohung spieltheoretisch untersucht. Die Investitionsentscheidung ist dabei abhängig von der Regulierungswahrscheinlichkeit und dem Regulierungsumfang, mithin dem Einfluß der Regulierung auf die Einnahmen des Marktsassen. Auf Grundlage der Erwartungen des Marktsassen bezüglich dieser Parameter wird er entscheiden, ob er investiert und welchen Preis er wählt. Dieser Preis wird unterhalb eines unregulierten Preises liegen, um eine Regulierung abzuwenden. Folglich wird gezeigt, daß schon die Androhung der Regulierung Übergewinne verhindert, ohne daß der regulatorische Eingriff selbst tatsächlich erfolgen muß. Der Regulierer wiederum kann die Investitionsentscheidung ebenso wie den vom Marktsassen gesetzten Preis durch Signale über Regulierungswahrscheinlichkeit und -preis beeinflussen. Diese Signale werden als optimal angesehen, wenn sie gleichzeitig die Investition ermöglichen und den Preis des Marktsassen minimieren.
urn:nbn:de:gbv:3:2-4127
Keywords: L43; L51; L96; 330; Regulierung; Investitionen; Telekommunikation; Netzindustrien; regulation; investment; telecommunication; network industries